Formation of NiFe2O4/Expanded Graphite Nanocomposites with Superior Lithium Storage Properties - Xiao, Yinglin; Zai, Jiantao; Tian, Bingbing; Qian, Xuefeng (Nano-Micro Letters, 2017)
A NiFe2O4/expanded graphite (NiFe2O4/EG) nanocomposite was prepared via a simple and inexpensive synthesis method. Its lithium storage properties were studied with the goal of applying it as an anode in a lithium-ion battery. The obtained nanocomposite exhibited a good cycle performance, with a capacity of 601 mAh g−1 at a current of 1 A g−1 after 800 cycles. This good performance may be attributed to the enhanced electrical conductivity and layered structure of the EG. Its high mechanical strength could postpone the disintegration of the nanocomposite structure, efficiently accommodate volume changes in the NiFe2O4-based anodes, and alleviate aggregation of NiFe2O4 nanoparticles. Highlights: 1 A NiFe2O4/expanded graphite (NiFe2O4/EG) nanocomposite was synthesized via a simple grinding and mixing process followed by annealing at a high temperature. The obtained NiFe2O4/EG nanocomposite showed superior lithium storage properties, with a capacity of 601 mAh g−1 at a current density of 1 A g−1 after 800 cycles. 2 The hybridNiFe2O4/EG nanostructure could efficiently improve the electrical conductivity and maintain structure stability, and its disintegration was delayed during discharge–charge processes, which led to a good cycling performance.